Social Policy: How is the Innovation in the Integrated Service and Referral System (SLRT) Services in the City of Bandung? - Achmad, Willya (Journal of Social Work and Science Education, 2024)
This study aims to analyze innovation in the implementation of the Integrated Service and Referral System (SLRT) as a social policy in the city of Bandung. SLRT is a holistic approach in providing social and welfare services to the community by integrating various existing programs and resources. This research focuses on innovations that have been implemented in SLRT and their impact on the effectiveness and efficiency of social service delivery. This research method involves a qualitative approach with descriptive methods. The results showed that the implementation of the Cetar Juara Integrated Service and Referral System in Bandung City had succeeded in overcoming the fragmented challenges of previous poverty reduction. Through an integrated approach, SLRT has provided fast and effective services to the poor and vulnerable. Innovations such as the development of integrated information systems, mobile applications, online services, and partnerships with the private sector have been significant in increasing the efficiency and accessibility of services. Thus, the results of the study indicate that SLRT Cetar Juara has had a positive, sustainable impact in overcoming poverty problems and improving people’s welfare.